Bioprotective role of Cladosporium tenuissimum counteracting heavy metal (chromium) stress in Triticum aestivum L. - Shahid, Sabrina; Ambrin,; Bibi, Shahida; Vasila, Sharipova; Asad, Fayaz; Gechev, Tsanko (Frontiers in Microbiology, 2025)
Heavy metal pollution, particularly from chromium (Cr), poses a significant threat to plant development and soil health. This study evaluated the efficacy of the rhizospheric fungus strain Cladosporium tenuissimum, isolated from the rhizosphere of Cannabis sativa, in enhancing the early growth and physiological resilience of Triticum aestivum L. (wheat) under chromium-induced stress. The strain Cladosporium tenuissimum demonstrated tolerance through substantial biomass retention in Czapek-Dox medium at chromium concentrations between 30 and 90 mg/L, mitigated the decrease in carotenoid and chlorophyll pigments, enhanced protein and sugar levels, and significantly promoted root and shoot growth in wheat under chromium stress. Additionally, fungal therapy reduced proline accumulation and restored indole-3-acetic acid (IAA) levels, indicating improved hormonal balance and reduced stress levels. Furthermore, Cladosporium tenuissimum (C. tenuissimum) maintained membrane integrity and regulated excess flavonoids by reducing electrolyte leakage. Under chromium stress, the activities of antioxidant enzymes were elevated; however, fungal inoculation moderated these activities to some extent. These findings indicate that C. tenuissimum may serve as a bioprotective agent, enhancing plant tolerance and mitigating Cr toxicity by regulating metabolic processes, physiological responses, and antioxidant activity.